Nutritional Values and Biochemical Traits of Rye (Secale cereale L.) Seeds, a Landrace from Matese Mountains (Southern Italy) - Nicola Landi; Sara Ragucci; Maria Giuseppina Campanile; Hafiza Z. F. Hussain; Stefania Papa; Antimo Di Maro (Foods)
Rye (Secale cereale L.) from Matese mountains is a local landrace cultivated in Southern Italy. To promote the benefits for the mountain economy, we report on the nutritional values (crude proteins, lipids, moisture, ash and total amino acids), metabolic traits (free amino acids, fatty acids and bioactive organic compounds) and mineral content of ‘segale del Matese’ seeds. Seeds were collected in 2023 and 2024 at two altitudes (~1000 and 150 m a.s.l.); these were analyzed, and the results were compared. Average data from two sites (crude proteins (9.6 g/100 g), lipids (1.3 g/100 g), ash (1.8 g/100 g), moisture (9.3 g/100 g) and carbohydrates (78.3 g/100 g)) show few significant statistical differences. The same trend was observed for total amino acid content, except for Glx (glutamic and glutamine), while statistical differences between the two sites were found among proteinogenic free amino acids. Moreover, segale del Matese’ is rich in polyunsaturated (linoleic and linoleic) and monounsaturated (oleic) fatty acids. Furthermore, total phenolic content, some bioactive compounds (i.e., gallic acid, vanillic acid, p-coumaric acid and ferulic acid) and radical scavenging activity were estimated. Finally, the seeds subjected to thermal treatment showed a decrease in anti-trypsin and anti-chymotrypsin activities, resulting in a favorable depletion of antinutritional factors.